IMPLEMENTASI METODE SIMPLE ADDICTIVE WEIGHTING (SAW) DALAM SISTEM PENDUKUNG KEPUTUSAN UNTUK MENENTUKAN DESA POTENSIAL PENYALAHGUNAAN NARKOBA - Fahriza, Wildan; Sulindawaty, Sulindawaty (Majalah Ilmiah Kaputama, 2020)
The problem of the dangers and effects of drugs or narcotics and drugs on life is increasingly troubling. The circulation of drugs has now reached an alarming stage, now it has touched the countryside. This stage is very worrying, hence the need for early supervision and prevention. Deli Serdang North Sumatra BNN previously acted and supervised by manually, this process took so long due to the large amount of data to be processed. Therefore the thought of the writer emerged to develop a computerized process to help the BNN Deli Serdang. Using the SAW method, the authors aim that the calculation process or data processing is faster so that it can maximize the time available so that the prevention process can be done as early as possible. This SAW method in the process has a calculation system by determining the ranking process, this ranking will be used as a decision-making by the Deli Serdang National Narcotics Agency in carrying out its duties.